2019
DOI: 10.15171/joddd.2019.033
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of roots enlarged with various rotary systems and filled with various sealers

Abstract: Background. This in vitro study compared the fracture resistance of roots instrumented either with ProTaper or One Shape rotary systems and filled with one of the silicate, epoxy resin or silicone-based sealers. Methods. Sixty single-rooted extracted mandibular premolars were decoronated to a length of 13 mm and then randomly divided into two main groups (n=30) in terms of the rotary system used for preparation. Group 1 samples were instrumented with the ProTaper Universal system up to a master apical file of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The main characteristics of the included studies are shown in Table 3 . Ten studies on the adaptation to root canal walls were included [ 30 , 31 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In comparison to the RBS, CSBs showed similar values of void volume marginal adaptation in five studies [ 32 , 36 , 37 , 38 , 39 ] whilst at the apical, mid, and coronal thirds, these values were high in three studies [ 31 , 35 , 41 ] and low in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the included studies are shown in Table 3 . Ten studies on the adaptation to root canal walls were included [ 30 , 31 , 32 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In comparison to the RBS, CSBs showed similar values of void volume marginal adaptation in five studies [ 32 , 36 , 37 , 38 , 39 ] whilst at the apical, mid, and coronal thirds, these values were high in three studies [ 31 , 35 , 41 ] and low in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies on fracture resistance were included [ 36 , 37 , 54 , 56 ] with values (FRV) mentioned in Newton unit and time intervals ranged from one week to a month. CSBs demonstrated similar FRVs when compated to RBS in three studies [ 36 , 37 , 56 ], whilst had superior values in one study [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…PTU ve One Shape (MicroMega, Besançon, Fransa) döner aletlerinin köklerin kırılma direncine olan etkisinin incelendiği başka bir çalışmada, PTU ile genişletilen köklerin daha az dirençli olduğu görülmüştür. 40 Kök kanallarının şekillendirilmesi süresince kalan dentin miktarının azalması ile dişlerin kırılma dirençlerinin azalması kaçınılmazdır, ancak döner aletler ile kök kanalları şekillendirilirken kırılma direncini etkileyen tek faktör kalan dentin miktarı değildir. Araştırmacılar NiTi döner aletlerin kesit ve eksen özelliklerine ve esnekliklerine bağlı olarak, dentin duvarıyla temas ettikleri bölgelerde oluşturdukları streslerle el aletlerine oranla, dentinde çatlak hattı, parsiyel veya vertikal kırık gibi dentin çatlaklarının oluşma riskinin arttığını ve bu çatlakların, kanal doldurma ve çiğneme kuvvetlerinin etkisiyle vertikal kök kırığına dönüşme ihtimalinin yüksek olduğunu belirtmişlerdir.…”
Section: Discussionunclassified
“…Bernardes et al (2009) also reported statistically significant differences between periapical radiographs and CBCT for the diagnosis of root fractures, with better results for CBCT. Although some authors suggest that root canal sealers can affect the resistance and the pattern of the fracture (Lertchirakarn, Timyam, & Messer, 2002), and that, especially glass ionomer cement can strengthen the root dentin (Trope & Ray, 1992), more recent investigations have concluded that sealers have no effect on fracture resistance (Yusufoglu, Akman, Akbulut, & Eldeniz, 2019).…”
Section: Discussionmentioning
confidence: 99%